ADJECTIVES AND THEIR TYPES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The primary goal of this project is to use EuroWordNet synsets for the semantic annotation of nominal and adjectival words within a portion of the SenSem corpus (BFF2003-06456). Acquiring selective restrictions associated with a sequence of verbal units requires the task of word sense disambiguation. One of the goals of the KNOW project (TIN2006-1549-C03-02) is this acquisition. In order to achieve this goal, we will also undertake two essential subtasks: creating classes of concepts (synsets), as the description of EuroWordNet contains too much detail. The outcome will be a data bank to work on the automatic disambiguation semantics in addition to making it possible to acquire selective restrictions.